In vitro properties analysis of potential probiotic of Isolated lactic acid bacteria from milk by-product - Jawan, Roslina; Abbasiliasi, Sahar; Mustafa, Shuhaimi; Halim, Murni; Ariff, Arbakariya (Faculty of Medicine & Health Sciences, Universiti Malaysia Sabah, 2018)
Background: Probiotics are live, microbial cells with several beneficial health effects on humans. The beneficial effect of probiotics mainly depends on their survival in the gastrointestinal tract. The health-promoting properties of certain LAB inhabiting the human gastrointestinal tract encouraged the food industry to develop new functional food products containing probiotic. Selection of a microbial strain for the incorporation into food products requires both in vitro and in vivo evaluations